Vedere con la mente: sogno, fantasia, allucinazione. Riflessioni cliniche e teoriche - Dell’Erba, Alice (Il sogno della farfalla, 2022)
Drawing from the latest epidemiological studies, this article aims to analyze dis-perceptive phenomena in the light of the clinical considerations formulated by the psychiatrist Massimo Fagioli. The author analyzes the theoretical contribution firstly proposed by Fagioli in the 1960s until the research carried out in the context of the Analisi collettiva in the early 1990s which aimed to free psychiatry from the burden of anti-scientific psychoanalytic ideas. Finally, the author highlights the importance to integrate classical psychopathological knowledge with the latest propositions elaborated in the human birth theory.